X-Ray scattering study of cellulosic arrangements in plant cell wall materials - Jarrett, Kevin J. (Curtin University, 2011)
Plant cell walls are the most important source of the polymer cellulose. The cell wall contains crystalline cellulose microfibrils embedded in a matrix of amorphous polymers. The most important of these amorphous polymers are the lignins and the hemi-celluloses. In this thesis we concentrate on the use of wide angle x-ray scattering as a tool to understand the important arrangements of cellulose in cell walls. Other experimental tools are used to supplement this information.